Strategic analysis of the forest carbon market in Brazil - Alves, Lucas Lamare Moreira (2024)
The forest carbon market in Brazil presents a complex scenario filled with challenges and opportunities. This study employed SWOT analysis to evaluate the dynamics of this market, based on the perceptions of 77 specialists from various professional fields. The analysis revealed that extensive forest cover and biodiversity preservation are significant strengths that position Brazil as a potential leader in the global carbon credit market. However, weaknesses such as illegal deforestation and fragile public policies undermine the effectiveness of conservation efforts. Opportunities include the growing international demand for carbon credits and the recognition of the importance of local communities in forest conservation. Nevertheless, external threats like land conflicts and political instability pose considerable risks. The study concludes that it is crucial to strengthen public policies and regulatory frameworks, promote technological innovation, and ensure the active inclusion of local and indigenous communities to guarantee the sustainability and growth of Brazil’s forest carbon market. The research suggests that despite significant challenges, Brazil can overcome these obstacles with the implementation of effective strategies.